Habitat Complexity Affects the Structure but Not the Diversity of Sessile Communities on Tropical Coastal Infrastructure - Chee, Su Yin; Yee, Jean Chai; Cheah, Chee Ban; Evans, Ally Jane; Firth, Louise B.; Hawkins, Stephen John; Strain, Elisabeth Marijke Anne (Frontiers in Ecology and Evolution, 2021)
Increasing human population, urbanisation, and climate change have resulted in the proliferation of hard coastal infrastructure such as seawalls and breakwaters. There is increasing impetus to create multifunctional coastal defence structures with the primary function of protecting people and property in addition to providing habitat for marine organisms through eco-engineering - a nature-based solutions approach. In this study, the independent and synergistic effects of physical complexity and seeding with native oysters in promoting diversity and abundances of sessile organisms were assessed at two locations on Penang Island, Malaysia. Concrete tiles with varying physical and biological complexity (flat, 2.5 cm ridges and crevices, and 5 cm ridges and crevices that were seeded or unseeded with oysters) were deployed and monitored over 12 months. The survival of the seeded oysters was not correlated with physical complexity. The addition of physical and biological complexity interacted to promote distinct community assemblages, but did not consistently increase the richness, diversity, or abundances of sessile organisms through time. These results indicate that complexity, whether physical or biological, is only one of many influences on biodiversity on coastal infrastructure. Eco-engineering interventions that have been reported to be effective in other regions may not work as effectively in others due to the highly dynamic conditions in coastal environment. Thus, it is important that other factors such as the local species pools, environmental setting (e.g., wave action), biological factors (e.g., predators) and anthropogenic stressors (e.g., pollution) should also be considered when designing habitat enhancements. Such factors acting individually or synergistically could potentially affect the outcomes of any planned eco-engineering interventions